Analisis Daya Saing dan Dampak Kebijakan Pemerintah terhadap Komoditas Karet di Kabupaten Pasaman - Putri, Afrina Zhilla; Tanjung, Faidil; Mutiara, Vonny Indah (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2025)
This study aims to analyze the competitiveness of rubber commodities through comparative and competitive advantages and analyze the impact of government policies on rubber commodities in Pasaman Regency. This study employed a survey method. The data analysis used in this study is quantitative using the Policy Analysis Matrix (PAM) measurement tool. The results of the study show that rubber commodities in Pasaman Regency have competitiveness based on competitive advantage and comparative advantage as seen from the PCR value of 0,65 and DRCR 0,32 which is smaller than one. The impact of the rubber output policy causes the private price of rubber to be lower compared to the social price. The impact of the production input policy causes the private price of tradable inputs to be higher than the social price. The impact of the input-output policy has caused a decrease in producer surplus, which means that there is no economic incentive to increase rubber production. Therefore, it is recommended to the Pasaman Regency government to provide counseling to farmers to increase productivity and quality of rubber by paying attention to cultivation techniques and the use of inputs so that they can obtain more competitive prices.